2022
DOI: 10.52547/unmf.19.12.930
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Incidence and Grade of Pressure Ulcer in Smokers and Non-Smokers Admitted to Intensive Care Unit

Abstract: Background & Aims: Pressure ulcer is a serious problem in patients admitted to the intensive care unit. It is associated with major complications such as prolonged length of stay and delayed recovery. The aim of this study was to compare the incidence and grade of pressure ulcers in smokers and non-smokers admitted to the intensive care unit. Materials & Methods:This study is an analytical cross-sectional study in which 120 patients in two groups (smokers (60) and non-smokers (60)) were selected by convenience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…In this study, it was shown that the history of underlying diseases such as diabetes and hypertension was associated with a significant increase in the risk of pressure ulcers in patients, which was consistent with the results of other studies. [15][16][17][18][19][20][21][22] Tabarsi and his colleagues also showed, like the present study, that the history of smoking among patients with pressure ulcers was significantly higher than among patients without pressure ulcers, and smoking was associated with an increase in the incidence of pressure ulcers in patients hospitalized in the ICU. 23 Smoking was one of the most powerful risk factors for pressure ulcers with an increase of about 400%.…”
Section: Discussionsupporting
confidence: 82%
“…In this study, it was shown that the history of underlying diseases such as diabetes and hypertension was associated with a significant increase in the risk of pressure ulcers in patients, which was consistent with the results of other studies. [15][16][17][18][19][20][21][22] Tabarsi and his colleagues also showed, like the present study, that the history of smoking among patients with pressure ulcers was significantly higher than among patients without pressure ulcers, and smoking was associated with an increase in the incidence of pressure ulcers in patients hospitalized in the ICU. 23 Smoking was one of the most powerful risk factors for pressure ulcers with an increase of about 400%.…”
Section: Discussionsupporting
confidence: 82%